IMPACT OF ENDURANCE SPORTS ON IRON LEVELS AND ANEMIA RISK IN FEMALE ATHLETES: A REVIEW - Alina Semianiuk; Lidia Jurczenko; Marta Miejska-Kamińska (International Journal of Innovative Technologies in Social Science, 2025)
Iron plays a crucial role in oxygen transport and energy metabolism, making it essential for athletic performance. Female endurance athletes are particularly susceptible to iron deficiency due to high training loads, menstrual blood loss, restrictive diets, and inflammation-induced hepcidin elevations. This review examines the prevalence, physiological mechanisms, and key causes of iron deficiency in female athletes. Evidence shows that iron losses occur through sweat, hemolysis, gastrointestinal bleeding, and exercise-induced inflammation. Heavy menstrual bleeding and relative energy deficiency in sport (RED-S) further increase risk. Additionally, genetic factors such as ACTN3 and HFE mutations may influence iron metabolism in athletes. Iron deficiency, even in the absence of anemia, is linked to impaired aerobic capacity, reduced endurance, and fatigue. Effective prevention and management strategies include regular monitoring, tailored dietary interventions, and iron supplementation when needed. Awareness of iron status is vital for female endurance athletes to sustain both health and performance.